KONTESTASI IDENTITAS PERISTIWA “KEMBALI” DALAM NOVEL RAPIJALI KARYA DEE LESTARI - Kurniawan, Heru; Somadayo, Samsu Rohman; Sholeh, Dwi Rohman; Sutardi, Sutardi (Dialektika: Jurnal Bahasa, Sastra, dan Pendidikan Bahasa dan Sastra Indonesia, 2023)
Returning as the title of the third series of novels, Rapijali by Dee Lestari is the primary key in understanding this novel in psychology and sociology. For this reason, this research was conducted to find and explain the events of Rapijali's identity contestation in a personal and social context so that the meaning of the philosophy conveyed through Rapijali can be understood from a psychological and sociological perspective. The method used is qualitative-textual research that examines the novel Rapjali: Kembali by Dee Lestari by looking at the psychological and sociological aspects using content analysis. Content analysis is related to reviewing aspects of the contestation of the events of Rapijali's return from the personal and social aspects of the characters and correlating them with psychological and sociological contexts. The result of the findings is the contestation of events in Rapijali: Again, it is built on a collective (sociological) consciousness that positions the Rapijali band as a home and family that can lead its members to find achievement and existence. From here, Rapijali is essentially home and a place for members to return to find their real (psychological) family and love. After returning to Rapijali, the end of love and family leads its members to find happiness in love and family in a personal and social context.